2009
DOI: 10.1103/physrevlett.103.066803
|View full text |Cite
|
Sign up to set email alerts
|

Threshold Voltage and Space Charge in Organic Transistors

Abstract: We investigate rubrene single-crystal field-effect transistors, whose stability and reproducibility are sufficient to measure systematically the shift in threshold voltage as a function of channel length and source-drain voltage. The shift is due to space-charge transferred from the contacts, and can be modeled quantitatively without free fitting parameters, using Poisson's equation, and by assuming that the density of states in rubrene is that of a conventional inorganic semiconductor. Our results demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The value of R C retrieved for the test structure considered here is 50 kΩ. The main-unknown in Equation (1) is μ b , which typically ranges from 10 to 30 cm 2 /V-s 7 9 . From Equation(1) and the measured I DS − V GS , Q free can be stated as a function of V GS , and related with the free carrier density (n free ) through Q free = q n free λ free .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The value of R C retrieved for the test structure considered here is 50 kΩ. The main-unknown in Equation (1) is μ b , which typically ranges from 10 to 30 cm 2 /V-s 7 9 . From Equation(1) and the measured I DS − V GS , Q free can be stated as a function of V GS , and related with the free carrier density (n free ) through Q free = q n free λ free .…”
Section: Resultsmentioning
confidence: 99%
“…The work is applicable not only to thin film field effect transistor (FET) but also the pervasive silicon metal-oxide-semiconductor FET (MOSFET). Given its significance as a crucial indicator of carrier transport and instability in FETs 4 5 6 7 8 9 10 , the conduction threshold has to be determined physically rather than by empirical means 11 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to inorganic semiconductors, the growth of molecular thin films commonly leads to the formation of polycrystalline layers which possess numerous defects such as stacking faults and grain or domain boundaries . Moreover, it has been shown that the molecular conformation and packing motif can be severely affected by the substrate so that the resulting characteristics of thin film devices are largely influenced by extrinsic, interface-related properties (e.g., trap-states) or space charge, and do not reflect the intrinsic properties of the OSC. Therefore, the main body of data on electronic properties of organic materials has been obtained from single crystal studies employing time-of-flight (TOF) measurements or single crystal field effect transistors (FET). , …”
Section: Introductionmentioning
confidence: 99%